Melampaui Teologi Naskh: Fitrah Manusia sebagai Dasar Dialog Antaragama dalam Pemikiran Abdulaziz Sachedina - Alexander Aur (Indonesian Character Journal, 2026)
One of the issues that frequently arises in interfaith relations is theological debate regarding various theological concepts. Theologians from every religion maintain various theological ideas on various topics such as the theology of salvation, the theology of scripture, the theology of revelation, and others. Differences in thought and efforts to build solid arguments on these various topics often hinder the establishment of dialogical relations between religions and among religious communities. Against this background, this article aims to explore Abdulaziz Sachedina's thoughts on the theological debate about ‘naskh’ and thoughts on human nature as the basis for interfaith dialogue. This type of research is qualitative and uses the methods of literature study and critical interpretation. Using these methods, this article contains a description of Abdulaziz Sachedina's thoughts and critical responses to them. The study finds that human nature as God's creation constitutes the foundation for equality among believers and for interreligious dialogue. As a contemporary Islamic thinker, Sachedina tries to go beyond ‘naskh’ theology by prioritizing the ontological status (nature) of humans as God's creation. Based on this ontological status, obstacles to interfaith dialogue due to differences in theological thinking on various topics within religions can be overcome. Thus, the goal of interfaith and interreligious dialogue can be achieved, namely, to glorify human dignity as God's creation.